Evaluation of oxidative stress parameters in older patients with urinary incontinence - Şahiner Zeynep; Eren Funda; Neşelioğlu Salim; Ceylan Serdar; Güner Merve; Hafızoğlu Merve; Karaduman Didem; Atbas Cansu; Ileri Ibrahim; Dikmeer Ayse; Okyar Baş Arzu; Balcı Cafer; et al. (Türk Biyokimya Dergisi)
Urinary incontinence (UI) is defined as any type of involuntary loss of urine. Pathophysiological changes that occur in the urinary system due to aging, especially ischemia, cause functional and structural changes in the urinary system. Oxidative stress is caused by an imbalance between the body’s oxidative radicals and antioxidant defense systems. In this study, we aimed to investigate the link between UI and oxidative stress indicators in older people.